2019
DOI: 10.1177/1074248419838502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Apixaban on INR in the Inpatient Population

Abstract: Direct oral anticoagulants (DOACs), particularly direct factor Xa inhibitors, have been associated with prolongation of the prothrombin time and the international normalized ratio (INR). Although DOACs do not require monitoring, elevations in the INR have been reported in in vitro and observational studies. The literature surrounding the extent of elevation and the clinical significance is limited. The objective of this study was to quantify the degree of INR elevation in hospitalized patients receiving apixab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…This patient’s baseline INR was 0.98 prior to initiation of apixaban and 1.84 prior to the first dose of warfarin, values that were above the median value reported in the previously mentioned study but within the observed range. 16 It is evident the presence of apixaban impacted this patient’s INR. This distinct increase in INR caused by apixaban makes using apixaban as a bridge to warfarin therapy challenging, as it is impossible to tell how much of the INR elevation is due to apixaban versus warfarin.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This patient’s baseline INR was 0.98 prior to initiation of apixaban and 1.84 prior to the first dose of warfarin, values that were above the median value reported in the previously mentioned study but within the observed range. 16 It is evident the presence of apixaban impacted this patient’s INR. This distinct increase in INR caused by apixaban makes using apixaban as a bridge to warfarin therapy challenging, as it is impossible to tell how much of the INR elevation is due to apixaban versus warfarin.…”
Section: Discussionmentioning
confidence: 86%
“…Apixaban therapy is not recommended during the transition due to the documented impact of oral factor Xa inhibitors on INR monitoring. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…INR elevation greater than 20 is rare with apixaban when compared to rivaroxaban [ 3 ]. Median INR of 1.4-1.7 in inpatients receiving apixaban has been reported [ 5 ]. A review of patients developing hemorrhagic cardiac tamponade in setting of apixaban use showed majority of these patients had elevated INR of 1.3-5.2 and renal dysfunction [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum concentration of apixaban is reached 1.5-3.3 hours after administration [ 4 ]. Kovacevic et al reported median INR of 1.4-1.7 in inpatient population receiving apixaban [ 5 ]. Plasma concentration of direct oral anticoagulants (DOACs) has been found to be correlating with that of the INR [ 6 ].…”
Section: Introductionmentioning
confidence: 99%